Osmotic stress and specific ion toxicity effects on seed germination and early seedling growth of eggplant (Solanum melongena L. cv. MTe 2) incurred by various salts - Mohd Arifin, Fateen Khaliessa; Nulit, Rosimah; Ibrahim, Mohd Hafiz; Idris, Leni Marlina (Research and Development Office, 2020)
Eggplant is an important crop but no study has been done regarding salt tolerance of eggplant (Solanum melongena L. cv MTe 2). Thus, the present work aimed to compare the effects of types and concentrations of salt solutions on seed germination and early seedling growth of MTe 2 eggplant. Ten sterilized MTe 2 eggplant seeds were treated with different concentrations (10, 25, 50, 100, 150, 200 mM) of NaCl, KCl, MgCl2 and MgSO4 in Petri dish with deionized water as control. The germination and seedling growth were significantly reduced as concentration of salt increased in NaCl and KCl. The germination performance and seedling growth were enhanced in 25 mM KCl. The seeds were unable to germinate even at the lowest concentration of MgCl2 and MgSO4. Recovery test revealed that while NaCl and KCl imposed an osmotic stress and induced seed dormancy, MgCl2 and MgSO4 imposed a specific ion toxicity.